Auditory Brainstem Response Findings in Children with Level 1 Autism Spectrum Disorder: A Comparative Study - Mariana de Medeiros Cardoso; Rudimar dos Santos Riesgo; Pricila Sleifer (International Archives of Otorhinolaryngology)
Introduction Autism spectrum disorder is a pervasive developmental disorder characterized by deficits in communication and social interactions, as well as repetitive behavioral patterns. Understanding the relationship between auditory brainstem response and hearing is crucial, considering the importance of sensory function. Auditory brainstem response testing is a tool that evaluates the auditory system from periphery to brainstem in response to an acoustic stimulus, providing important information about the auditory pathways.